High density and super ultra-microporous-activated carbon macrospheres with high volumetric capacity for CO2 capture - Liu, Jingjing; Liu, Xin; Sun, Yuan; Sun, Chenggong; Liu, Hao; Stevens, Lee A.; Li, Kaixi; Snape, Colin E. (Wiley, 2017)
Activated carbon (AC) spheres with a diameter of 1.0–2.0 mm are synthesized from coal tar pitch for postcombustion carbon capture. The as-prepared AC macrospheres after KOH activation are found to possess extraordinarily developed microporosity of which 87% is ultra-microporosity with pore diameters less than 0.8 nm. Despite the relatively low surface area of just 714 m2 g−1 with a pore volume of 0.285 cm3 g−1, the macrospherical carbon adsorbents achieve exceedingly high CO2 uptake capacities of 3.15 and 1.86 mmol g−1 at 0 and 25 °C, respectively, with a CO2 partial pressure of 0.15 bar. Cyclic lifetime performance testing demonstrates that the CO2 uptake is fully reversible with fast adsorption and desorption kinetics. More importantly, due to their high bulk density of ≈1.0 g cm−3, the AC macrospheres exhibit extremely high volumetric CO2 uptakes of up to 81.8 g L−1 at 25 °C at 0.15 bar CO2, which represents the highest value ever reported for ACs. The high ultra-microporosity coupled with the potassium-modified physiochemical surface properties is found to be responsible for the outstanding CO2 adsorption performance of the pitch-based AC macrospheres.